PEMBINAAN ORGANISASI KEPEMUDAAN DI DINAS PARIWISATA, KEBUDAYAAN, KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Dadan Setia Nugraha; Agung Abdul Jani; Deby Octaviana; Farhan Nur Fadilah; Saniyyah Nur Aini; Syifa Agnia Elianto (Journal Of Regional Public Administration (JRPA), 2022)
The development of youth groups is a strategic matter to utilize the potential of youth for successful development. This study also aims to determine the Development of Youth Organizations to know the inhibiting factors in carrying out Youth Group Development and the efforts made to overcome obstacles to Youth and Sports Group Development at the Youth and Sports Culture Tourism Office of Sumedang Regency. This research was conducted using a qualitative method with a descriptive type. Data collection techniques are carried out through library research and field studies which include: observation, interviews, and documentation. Determination of samples/informants in this study was carried out using purposive sampling as many as 4 people. Meanwhile, the data processing procedure used Miles and Huberman model data analysis with the following steps: data reduction, data presentation, and verification.The final result of this study concludes that the Development of Youth Groups at the Department of Tourism, Culture, Youth and Sports, Sumedang Regency has been running well but not optimally. This is indicated by the following findings: (1) The attendance rate of youth organizations only reaches 75%. (2) The government does not provide infrastructure that is intended for youth organizations. (3) The government is not sufficient about what budget is needed by the personnel organization so that the budget is not sufficient. Suggestions for this research are to further improve the quality of group coaching by always paying attention to various things such as facilities and infrastructure that affect the smooth process of Youth and Sports Group Development at the Tourism, Culture, Youth and Sports Office of Sumedang Regency so that in the future its implementation can run better. The Department of Tourism, Culture, Youth and Sports should seek to increase the budget ceiling for youth development so that the implementation of coaching can be more effective. The Department of Tourism, Culture, Youth and Sports should provide and improve facilities and infrastructure to support youth organizational development activities.